Od recesji do reindustrializacji. Nowy priorytet rozwoju społeczno-gospodarczego Unii Europejskiej w dobie narastającej konkurencji globalnej - Walkowski, Maciej (Rocznik Integracji Europejskiej, 2015)
After over a dozen years of the illusory belief in the success of the „knowledge-based economy", mainly based on knowledge-intensive services (KIS), and the e-economy development model, EU policymakers noticed the error of de-industrialisation initiated in the late 1980s. Both at the level of member states and that of European institutions – under the banner of re-industrialisation – it was decided to return to the idea of developing a modern and competitive European industry. Deindustrialisation meant that European corporations transferred their labour-intensive production to the ‘largest factory of the world,’ namely China and other emerging markets of South and East Asia. This was associated with the loss of thousands of jobs in European industries, increasing unemployment and social discontent. In the paper, the author describes and evaluates the idea of the re-industrialisation of the European economy and discusses the most important initiatives necessary to implement the vision of a modern, innovative and industrial Europe.